The Integral Nature of the Liturgical Formation of the People of God in Light of the Apostolic Letter "Desiderio Desideravi" - Megger, Andrzej (Verbum Vitae, 2025)
This article focuses on the concept of liturgical formation, which Pope Francis identified as an urgent need for the entire Catholic Church in his Apostolic Letter Desiderio Desideravi. Since the liturgy is a concrete reality and not a mere idea, formation presupposes the prior fulfillment of conditions which are faith and awareness of the nature of the liturgy, as well as the proper disposition of a person based on Christian anthropology. First, the broad perspective of the liturgy was presented, which is the work of the entire Holy Trinity, expressed in the Paschal Mystery of Jesus Christ, whose goal is to bring every creature into communion with the Creator. Man participates in this work as a corporeal-spiritual being with the ability to understand symbols and capable of liturgical action. Formation for participation in the liturgy involves not only intellectual preparation, but also ascetical preparation, that is, the involvement of the whole person and all the faculties of man in the process of becoming like Christ, the source of which is the celebration. Formation through participation in the liturgy applies to all conditions and forma of Christian life; therefore, based on the Apostolic Letter and the Church’s teaching, a general characterization of the formation of the various groups of the faithful has been made. On this basis, liturgical formation is an integral process for the formation of the human person as a liturgical person, capable of realizing his vocation which comes from the fact of creation.